The Battle of the Sex Differences / We Talk to Cordelia Fine and Simon Baron-Cohen Reviews her New Book The Gender Delusion - Sutton Jon; The British Psychological Society (2010)
Collective Solutions to a Global Problem, Being Proactive at Work - Blessing or Bane?, Eye on Fiction: No Self Without Self-Delusion, Opinions: Occupational Psychology in a Changing World.